FACTORS AFFECTING IMPLEMENTATION OF STANDARD OPERATING PROCEDURES TRACER OF MEDICAL RECORD OF ISLAMIC HOSPITAL SURABAYA - Lilis Masyfufah; Rumianah . (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
One of the efforts in conducting orderly administration in the hospital is how to monitor patient medical records to improve the quality of health services in the hospital. It aims to monitor the patient's medical record if not found in the medical record room. Standard Operational Procedure (SOP) medical record tracer already exists but in reality not implemented by medical record officer of outpatient registration Hospital Islam Surabaya. Not implemented the use of medical records tracer resulted in officers often have difficulty in monitoring the existence of medical records that came out of the storage rack or tucked and entered into another number. Therefore the purpose of this study is to analyze factors related to the implementation of SOP tracer outpatient medical records at Surabaya Islamic Hospital in 2017. This type of research is quantitative analytics. The sample of this study is total sampling of outpatient medical record registration officer at Surabaya Islamic Hospital. Data collection method used was questionnaire interviewed. The result of this research is concluded that the factors related to SPO tracer implementation are man factor, that is knowledge with significance value 0,040 (<0,05).